Impact of hepatic steatosis on liver stiffness measurement by vibration-controlled transient elastography and its diagnostic performance for identifying liver fibrosis in patients with chronic hepatitis B - Zhiyuan Chen; Ye Huang; Yan Zhang; Dongjing Zhou; Yu Yang; Shuping Zhang; Huanming Xiao; HaiXia Li; Yupin Liu (Insights into Imaging)
Abstract Objectives To explore the impact of hepatic steatosis measured by MRI-proton density fat fraction (MRI-PDFF) on liver stiffness measurement (LSM) value and its diagnostic performance for staging liver fibrosis in patients with chronic hepatitis B (CHB). Methods A total of 914 patients with CHB who underwent liver biopsy and MRI-PDFF were retrospectively reviewed. The influence of MRI-PDFF on LSM value was assessed using univariate and multivariate linear analyses. To assess the influence of liver steatosis on the diagnostic performance of LSM, a series of ROC analyses were performed and compared by stratifying patients into non-steatosis (PDFF < 5%) and steatosis (PDFF ≥ 5%) groups according to MRI-PDFF values. The effects of different LSM cut-off values on the false-positive rate in the steatosis cohort were compared using McNemar’s test. Results LSM values were significantly affected by MRI-PDFF in the entire cohort (B-coefficient: 0.003, p < 0.001), F1 cohort (B-coefficient: 0.005, p < 0.001), and F2 cohort (B-coefficient: 0.003, p = 0.002). Hepatic steatosis was not observed to have a significant influence on the ROC curve of LSM for staging liver fibrosis. Compared with using the cut-off values for the CHB cohort, using relatively higher cut-off values for hepatic steatosis significantly improved the false-positive rate of LSM in the steatosis cohort. Conclusion Steatosis significantly influenced LSM, with a higher value in the early stage of liver fibrosis but did not affect the diagnostic efficiency of LSM for staging liver fibrosis. Moreover, using relatively high cut-off values significantly improved the false-positive rate of LSM in CHB patients with steatosis. Clinical relevance statement The identified correlation between MRI-PDFF and VCTE-measured LSM is not clinically relevant since the diagnostic performance of LSM in staging liver fibrosis is not affected by steatosis. A higher cut-off should be applied in CHB patients with steatosis to improve the false-positive rate. Key Points Steatosis can affect liver stiff measurement (LSM) values in the early stage of liver fibrosis. The diagnostic performance of LSM in staging liver fibrosis is not affected by steatosis. LSM’s cutoffs should be increased in patients with steatosis to improve the false-positive rate. Graphical Abstract